ANALISIS WACANA TAJUK RENCANA HARIAN KOMPAS MENGENAI KEBIJAKAN NORMAL BARU PEMERINTAH INDONESIA - Hutajulu, Elisa Fransiska; Kaligis, Retor AW (Istek Widuri Jakarta, 2021)
This study examines the construction of the Kompas Daily editorial text regarding the Indonesian government's new normal policy. This study aims to find out how the construction of the Kompas Daily editorial text regarding the Indonesian government's new normal policy. This study uses a qualitative descriptive method with discourse analysis of Teun A Van Dijk, and uses documentation studies and in-depth interviews for data collection. Through the analysis, it was found that, in terms of the text dimension, in general the seven editorials of the Kompas Daily took the theme of things that Indonesia should pay attention to and implement in order to implement the new normal policy. In the dimension of social cognition, the editorial of Kompas Daily is made by combining the ideology, understanding, knowledge, and point of view of Kompas and that of an editorial writer as an individual, which will later produce an editorial that is expected to be wise. In the context dimension, it is found that the discourse circulating in the community is the same as the discourse raised in the seven editorials regarding the new normal policy of the Indonesian government with various perspectives, including the pros and cons of this policy.